Research on Vibration Mechanism of Plant Cell Membrane with Ultrasonic Irradiation - 曹辉 黄婉君 乔佳婷 王云鹏 赵海君 (Chinese physics letters, 2015)
The vibration mechanism of the cell membrane of plant seeds is analyzed based on the physical effect of ultrasound. The vibration model of cell rectangular membrane of plant seeds is then proposed and the expression of resonance frequency is obtained. The resonance frequency of cell membrane under the built model in the case of knowing the surface tension, surface density and size of cell membrane are calculated. The results of the theoretical calculations are in accordance with the previous experimental results. The built vibration model of cell membrane has certain rationality and certain reference significance to the determination of parameters in ultrasonic breeding in physical agriculture.